Study of Association between Factor XI Polymorphism and Recurrent Miscarriage in Iran Helal Infertility Center (Rouyesh) Patients - Sonia Hajizadeh; Hamid Choobineh; Azadeh Omidkhoda; Shaban Alizadeh; Mohammad Jafar Sharifi; Zeinab Kavosh (Tehran University of Medical Sciences, 2019)
Background and Aim: Recurrent pregnancy loss(RPL) is known as two or three pregnancy losses before 20th week of pregnancy. RPL accounts for 5% of abortions in women and has a devastating effect on the marital status of families. One of the reasons for RPL is hemostatic complications; thus, we studied the correlation between factor XI polymorphism and RPL in patients who referred to Helal Infertility Center(Rouyesh). Material and Methods: In this case-control study, 144 patients with a history of miscarriages(at least two) and 150 healthy female with a minimum of one successful birth and no abortion were enrolled. DNA extraction was taken from leukocytes of whole blood. To investigate the polymorphisms, polymerase chain reaction was run, and the presence of polymorphism was analyzed using RFLP method. Results: Regarding FXI polymorphism, TT, CT, and CC genotype frequencies were 59.7%, 36.1%, and 4.2%, respectively. In healthy control group, the TT, CT, and CC frequencies were 45.3%, 49.4%, and 5.3%, respectively. Conclusion: TT homozygote genotype could be an RPL risk factor(p<0.05); however, in its CT heterozygote form, C allele could have a protective role against RPL.